The Specific Heat of Liquid Helium. Issue 3 (15th April 2016) - Molinari, Vincenzo; Mostacci, Domiziano; Ganapol, Barry D.
ABSTRACT: Starting from the modified Lennard–Jones potential, a method is proposed to calculate the internal energy in liquids, and from this the specific heat. The method is applied to liquid helium-4 and the well-known shape of the "lambda point" is reproduced.